Immunoadjuvant therapy in the regulation of cell death in sepsis: recent advances and future directions - Islam, Md. Monirul; Watanabe, Eizo; Salma, Umme; Ozaki, Masayuki; Irahara, Takayuki; Tanabe, Subaru; Katsuki, Ryusuke; Oishi, Dai; Takeyama, Naoshi (Frontiers in Immunology, 2024)
Sepsis is characterized by a concomitant early pro-inflammatory response by immune cells to an infection, and an opposing anti-inflammatory response that results in protracted immunosuppression. The primary pathological event in sepsis is widespread programmed cell death, or cellular self-sacrifice, of innate and adaptive immune cells, leading to profound immunological suppression. This severe immune dysfunction hampers effective primary pathogen clearance, thereby increasing the risk of secondary opportunistic infections, latent viral reactivation, multiple organ dysfunction, and elevated mortality. The types of cell death include apoptosis (type I programmed cell death), autophagy (type II programmed cell death), NETosis (a program for formation of neutrophil extracellular traps (NETs)) and other programmed cell deaths like pyroptosis, ferroptosis, necroptosis, each contributing to immunosuppression in distinct ways during the later phases of sepsis. Extensive apoptosis of lymphocytes, such as CD4+, CD8+ T cells, and B cells, is strongly associated with immunosuppression. Apoptosis of dendritic cells further compromises T and B cell survival and can induce T cell anergy or promote regulatory Treg cell proliferation. Moreover, delayed apoptosis and impaired neutrophil function contribute to nosocomial infections and immune dysfunction in sepsis. Interestingly, aberrant NETosis and the subsequent depletion of mature neutrophils also trigger immunosuppression, and neutrophil pyroptosis can positively regulate NETosis. The interaction between programmed cell death 1 (PD-1) or programmed cell death 1 ligand (PD-L1) plays a key role in T cell modulation and neutrophil apoptosis in sepsis. The dendritic cell growth factor, Fms-like tyrosine kinase (FLTEL), increases DC numbers, enhances CD 28 expression, attenuates PD-L1, and improves survival in sepsis. Recently, immunoadjuvant therapies have attracted attention for their potential to restore host physiological immunity and homeostasis in patients with sepsis. This review focuses on several potential immunotherapeutic agents designed to bolster suppressed innate and adaptive immune responses in the management of sepsis.